The logic of «pure knowledge» and conceptual understanding of principle of causality in normativism - A. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
The paper is devoted to the analysis of the philosophical foundations of Hans Kelsen’s normativism, presented in the arguments of the Marburg school of neocantianism. With the help of the reconstruction of the «logic of pure knowledge» by H. Cohen, the conceptual apparatus of normativism is reinterpreted. Special attention is paid to the conceptual analysis of the principle of causality in scientific knowledge, the roots of which are found in ancient philosophical thought and mythology with the idea of retribution. As additional arguments for the legal methodology the arguments of the normativist theory are given, justifying a methodological alternative to the search for cause-and-effect relationships in legal reality